Effect of mobile learning on students' satisfaction, perceived usefulness, and academic performance when learning a foreign language - Togaibayeva, Aigulden; Ramazanova, Dinara; Yessengulova, Meiramgul; Yergazina, Aliya; Nurlin, Akylbek; Shokanov, Ruslan (Frontiers in Education, 2022)
While the use of mobile technologies for foreign language learning is gaining momentum, little is known about the various factors that can influence the effectiveness of mobile technologies in relation to student performance in learning a foreign language. The study aims to examine various aspects of mobile learning affecting students’ satisfaction, the presumed usefulness of using mobile technologies in learning a foreign language, as well as students’ academic performance. Achieving the established study objectives involved using a set of methods, which included theoretical, empirical, and methods of mathematical statistics for quantitative and qualitative processing of research results and statistical verification of their objectivity with Spearman’s rank correlation method. The relevance of using mobile technologies in teaching foreign languages to future philologists is substantiated. An experimental study of the effect of various aspects of mobile learning on students’ perceived satisfaction in learning a foreign language, their perception of the usefulness of mobile learning, and academic performance is carried out. Different aspects (individual factors) of mobile learning, such as motivation to use mobile learning, the relevance of content provided by mobile learning to student needs, the ubiquity of mobile learning, and self-efficacy, have an impact on students’ perceived satisfaction in learning a foreign language and their perception of the usefulness of mobile learning, as well as academic performance. The obtained results present teachers and students with useful information on mobile learning in the context of philological education.